The study of the influence of the state of the oral cavity on the psycho-emotional status of students of the Faculty of Dentistry «Privolzhsky Research Medical University» of the Ministry of Health of the Russian Federation - O. A. Uspenskaya; S. A. Spiridonova; A. V. Sukhova; O. M. Bragina (Эндодонтия Today)
Aim. Is to evaluate the dental status of students studying at the Dental Faculty of FSBEI HE PRMU MOH of the Ministry of Health of the Russian Federation and to identify its effect on the psycho-emotional state.Materials and metods. The study involved 500 students of the Faculty of Dentistry FSBEI HE PRMU of the Ministry of Health of the Russian Federation. All subjects, in accordance with the index of the OHI-S index, were divided into three groups depending on the index of cavity hygiene: the first group, the OHI-S index was less than 0.7 points (good level of oral hygiene) – group 1A-in it included 125 Russian students (50%), group 1B-95 of foreign students (38%); The 2nd group, the OHI-S indicator is from 0.8 to 1.6 points (a satisfactory level of oral hygiene) – group 2A – it includes 80 Russian students (32%), group 2B – it includes 65 foreign students (26%); Group 3: the OHI-S indicator is more than 1.7 points (unsatisfactory index of oral hygiene) – group 3A – it included 45 Russian students (18%), group 3B – it included 90 foreign students (36%). The prevalence and intensity of the carious process was evaluated using the DMF index, the oral hygiene was assessed using the OHI-S index according to J. Green, J. Vermillion, the periodontal tissue condition was assessed using the CPI index (complex periodontal index), and Kechka bleeding index. The following tests were used to assess the psychoemotional status: Spilberger-Hanin anxiety test, HAM test, suggestibility and stress tolerance test. To assess the results and conduct comparative characteristics, we used the analysis of variance, the Biostat program, and also the Microsoft Excel software product using the Student criterion.Results. The prevalence of dental caries is 98%. The average rate of tooth decay in Russian students was 5.8 ± 0.23, and in foreign students 7.6 ± 0.3. A study of the CPI index revealed with a satisfactory level of hygiene: mild periodontal tissue lesions in 28% of Russian students, 4% have a medium periodontal lesion, 18% of foreign students have a mild periodontal tissue lesion, 6% have an average periodontal lesion; with an unsatisfactory level of hygiene, 16% of Russian students have an average degree of periodontal damage and 2% have a severe periodontal disease, 32% of foreign students have an average periodontal disease and 4% have a severe periodontal disease. Analysis of the HAM test showed a decrease in the number of foreign students by the 5th year of study with a high level of well-being, for Russian students by the 5th year of study, the average level of well-being, activity and mood was characteristic. A low level was characteristic of 2nd year students of the Russian and foreign departments.Conclusions. A study of the psychoemotional state of students at a medical university revealed a high level of activity, well-being and mood among students of the Russian department and average rates among students of a foreign department, which is explained by low oral hygiene and high caries intensity, a change in climatic conditions and place of residence, a change in diet, emotional and physical overload.